2019
DOI: 10.11622/smedj.2019029
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of blood transfusion for Caesarean sections in pure placenta praevia pregnancies

Abstract: METHODSThis case-control study was conducted after approval by our institutional review board. We included subjects with placenta praevia who underwent Caesarean delivery at a gestational age of INTRODUCTION This study aimed to evaluate associated factors of blood transfusion for Caesarean sections in pure placenta praevia pregnancies.METHODS A case-control study was conducted among 405 pregnant women with placenta praevia who underwent Caesarean delivery between August 2004 and December 2013. 135 of the women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A recent study listed risk factors associated with blood transfusion in PP cases as previous cesarean section, anterior PP, major PP, preoperative bleeding, and emergency cesarean section [23]. In our current study, in which data on antenatal bleeding episodes and estimated blood loss were missing, we found that the need for blood transfusion in PP cases was associated with the increasing number of previous cesarean sections, emergency cesarean section, PAS, uterine artery ligation and general anesthesia.…”
Section: !"#$%And ?(And@8$50$%and $03%"-and-%-%220+3and "3"$:202and A...supporting
confidence: 42%
“…A recent study listed risk factors associated with blood transfusion in PP cases as previous cesarean section, anterior PP, major PP, preoperative bleeding, and emergency cesarean section [23]. In our current study, in which data on antenatal bleeding episodes and estimated blood loss were missing, we found that the need for blood transfusion in PP cases was associated with the increasing number of previous cesarean sections, emergency cesarean section, PAS, uterine artery ligation and general anesthesia.…”
Section: !"#$%And ?(And@8$50$%and $03%"-and-%-%220+3and "3"$:202and A...supporting
confidence: 42%
“…Multivariable logistic regression analysis identified four significant independent risk factors for intraoperative massive hemorrhage in patients with placenta previa and accreta, but we chose to include the other six indictors with clinical significance into the scoring system. It has been reported that the clinical indictors included advanced age, gravidity, history of CS, and preoperative anemia are significant in predicting the risk of intraoperative massive hemorrhage . MRI indictors included empty vascular shadow of the uterus and attachment position of the placenta and are closely related to placenta accreta, and which could cause intraoperative massive hemorrhage .…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of T 2 dark intraplacental bands is higher than the others, so it was selected into the multivariable logistic regression, as well as the length of the cervical canal and dilation of the cervical canal. Then, according to the relevant literature on risk factors of massive bleeding and the clinical practice experience of the doctors, the following 10 indicators potentially associated with intraoperative massive hemorrhage were identified as potential risk factors: clinical maternal age, preoperative hemoglobin level, gravidity number, number of CS, and MRI T 2 dark intraplacental bands, cervical canal length, placenta thickness on the uterine scar area, empty vascular shadow of the uterus, low signal discontinuity in the muscular layer of the posterior wall of the bladder, and attachment position of the placenta were imputed in the multivariable logistic regression analysis . The specific measurement methods and images are shown in Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with excessive bleeding during surgery often need a blood transfusion. In this study, 4 units of ES were prepared before surgery, as described in another study [ 17 ]. Among our patients, the volume of erythrocytes transfused was higher in group 1 than in group 2 patients (0.8 units higher; P =0.014).…”
Section: Discussionmentioning
confidence: 99%